Brace, Ashley. Phantom fires in St. John's. - Jarvis, Dale Gilbert, 1971- (2011)
Recording of a ghost story told by Ashley Brace, a Grade 8 student at St. Peter's Junior High. Recorded in the Newman Wine Vaults Provincial Historic Site as part of the Young Folklorists Program run by the Heritage Foundation of Newfoundland and Labrador in May, 2011. Ashley writes, "This story comes from downtown St. John's on one of the oldest lanes in the city, Willicott's Lane, which is in the neighbourhood that burned down in the great fire of 1892. I found the story on the Haunted HIke website. In the story, it tells the tale of a house that is said to be haunted by a phantom fire. I chose to share this story because it was very unique and I had never heard anything like it before."